Monte carlo simulation of vapor - liquid equilibria of hydrogen using ab initio intermolecular potentials - Tat, Pham Van (Vietnam Journal of Chemistry, 2014)
The vapor-liquid equilibria of pure fluid hydrogen were predicted by Gibbs ensemble Monte Carlo simulation techniques using our two different ab initio intermolecular pair potentials. The ab initio intermolecular interaction potentials were obtained from coupled-cluster calculations, using the CCSD(T) level of theory and Dunning's correlation consistent basis sets aug-cc-pVmZ (m =2, 3) [9]. The phase diagram, critical properties, thermodynamic properties, vapor pressures and orthobaric densities based on them are found to be in very good agreement with experimental data. Keywords: Vapor-liquid equilibria, Gibbs ensemble Monte Carlo simulation, ab initio potentials.